2015
DOI: 10.1103/physrevb.92.085433
|View full text |Cite
|
Sign up to set email alerts
|

Topologically confined states at corrugations of gated bilayer graphene

Abstract: We investigate the electronic and transport properties of gated bilayer graphene with one corrugated layer, which results in a stacking AB/BA boundary. When a gate voltage is applied to one layer, topologically protected gap states appear at the corrugation, which reveal as robust transport channels along the stacking boundary. With increasing size of the corrugation, more localized, quantum-well-like states emerge. These finite-size states are also conductive along the fold, but in contrast to the stacking bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 69 publications
0
49
1
Order By: Relevance
“…Similar arguments apply for TDBG structures with C 3 symmetry, which also have at most two-dimensional irreps. In fact, the sublattice-andlayer-exchange symmetry is broken by any perturbation that allows to distinguish between layers, such as a potential difference [41][42][43] or another layer(s) coupled with a twist 23 . This symmetry breaking results in the opening of a gap between the AB-related bands, due to the different atomic coordination environments of the two AB layers.…”
Section: Resultsmentioning
confidence: 99%
“…Similar arguments apply for TDBG structures with C 3 symmetry, which also have at most two-dimensional irreps. In fact, the sublattice-andlayer-exchange symmetry is broken by any perturbation that allows to distinguish between layers, such as a potential difference [41][42][43] or another layer(s) coupled with a twist 23 . This symmetry breaking results in the opening of a gap between the AB-related bands, due to the different atomic coordination environments of the two AB layers.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, when a domain wall (DW) divides bilayer graphene into AB and BA stacking domains, a pair of states appears at each valley, connecting the valence and conduction band continua through the energy gap ( Fig. 1 right) [21][22][23]. These gapless states are topologically protected if the valley index is conserved.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been recently shown that slightly twisting the two layers dramatically changes the band structure, allowing the observation of unconventional superconductivity 8 and Mott insulating behavior 18 . An addition to these diverse properties of graphene bilayers are the recently identified topologically protected states at boundaries between AB and BA stacked graphene bilayers [19][20][21][22] . In thicker graphene flakes, the physics can be expected to be even richer, since naturally two stable forms of stacking, Bernal (or ABA, Fig.…”
mentioning
confidence: 99%